A subjetividade do adolescente renal crônico - Ribeiro, Sâmia Karine Moraes (2003)
Understanding of the complexities in the process of health and disease requires an in-depth reading of the relationships established between the person who becomes ill and his infirmity. Although the subjects’ expressions may be considered to exist in a social-historical-cultural context, it must be emphasized that the manner in which they confer meaning to their illnesses stems from a unique and significant experience. The main objective of this study is to identify the subjective meaning attributed by the adolescent chronic renal patient to his disease, by approaching both subjectivity and the process of health and disease. This was achieved through use of the Qualitative Epistemology reference developed by Rey (1996, 1997, 1999). Fieldwork was performed using five adolescents. The process of information construction led to recognition of three central themes: 1. The Diagnosis; 2. The Subject and The Treatment; 3. The Adolescent Chronic Renal Patient. Articulation of these three themes enabled reflection on the understanding obtained regarding that which is Chronic Renal Insufficiency and its development, based on the perception of the adolescents bearing this infirmity, which then allowed for the comprehension of illness as a fundamentally subjective process. In conclusion, some questions arise regarding current practices in the hospital that allow for the rethinking of the assistance provided to the chronic renal patient, thus enabling the emergence of effective interventions which could yield a better quality of life for these patients.